Unusual case of phenylketonuria with atypical brain magnetic resonance imaging findings - Medici, Conrado; Varacchi, Claudio; Gonzalez, Gabriel; Lemes, Aida; Cerisola, Alfredo; Pedemonte, Virginia; Blau, Nenad (Journal of child neurology, 2013)
Phenylketonuria is a treatable inborn error of amino acid metabolism caused by deficiency of the enzyme phenylalanine hydroxylase, responsible for converting phenylalanine to tyrosine. We report a 10-month-old boy with psychomotor regression and infantile spasms. He was diagnosed with classic phenylketonuria and West syndrome. Treatment was initiated with phenylalanine-restricted diet and vigabatrin. After 5 months of treatment, he persists with developmental delay, severe hypotonia, swallowing disorder, and drug-resistant epilepsy. Brain magnetic resonance imaging showed the typical abnormalities in supratentorial white matter and exceptional infratentorial and basal ganglia compromise. Severity of white matter abnormalities and neurologic symptoms correlates with blood levels of phenylalanine. Infratentorial changes occur in severe cases. Other mechanisms could take part in cases like this with atypical neuroimaging abnormalities of the basal ganglia.
First published September 10, 2012
Gesehen am 09.07.2021